La señalética y la orientación del turista en el cantón Ventanas, de la provincia de los Ríos - Vega Balcázar, Juan Carlos (2018)
The present final report with the theme: THE SEALING AND THE ORIENTATION OF THE TOURIST IN THE CANTON VENTANAS, OF THE PROVINCE OF LOS RÍOS, served to carry an adequate and feasible process of the development of the investigation, the same had like general objective to determine the signage in the tourism orientation of the Ventanas canton, to facilitate the displacement of visitors to the resources and tourist attractions of the town linked to their respective specific objectives which are systematizing the scientific theoretical basis for the development of chapters I and II, a general methodology for the structuring of tourist signage, we worked with a methodological design which allowed to carry out a process of the respective activities to be followed in post of the development of the research, the surveys and design of the signage were carried out. In conclusion it was determined that signage plays a very important role in the world of tourism and will also facilitate the movement of tourists, that is why tourist signage in tourist orientation is very important as it will generate socio-economic development and provide valuation of the cultural, natural resources and services that the canton of Ventanas has. Once the problems of this investigation became evident, a proposal was applied based on a guide for the design, construction and repair of signage in harmony with the environment to guide tourists visiting the canton of Ventanas, thus achieving the tourist development of the